The Path through Math: Course Sequences and Academic Performance at the Intersection of Race-Ethnicity and Gender - RIEGLE-CRUMB, CATHERINE (2006)
Using new national data from Adolescent Health and Academic Achievement (AHAA), this article examines high school math patterns for students of different race-ethnicity and gender. Compared with white males, African American and Latino males receive lower returns from taking Algebra I during their freshman year, reaching lower levels of the math course sequence when they begin in the same position. This pattern is not explained by academic performance, and, furthermore, African American males receive less benefit from high math grades. Lower returns are not observed for minority female students, suggesting that more attention to racial-ethnic inequality in math among male students is needed.